SALGIN DÖNEMİNDE İLAHİYAT FAKÜLTESİ ÖĞRENCİLERİNİN UZAKTAN EĞİTİME YÖNELİK GÖRÜŞLERİNİN İNCELENMESİ - ECE, NESİBE (Fırat Üniveristesi, 2022)
Bu çalışmanın amacı İlahiyat Fakültesi öğrencilerinin uzaktan eğitime yönelik görüşlerini belirlemektir. Araştırma nitel desenle yürütülmüştür. Çalışmanın yapısı göz önünde bulundurularak çalışma grubu oluşturulurken kolay ulaşılabilir durum örnekleme yöntemi tercih edilmiştir. Araştırma, 2020-2021 Bahar Yarıyılı Döneminde Fırat Üniversitesi İlahiyat Fakültesi hazırlık, 1, 2, 3 ve 4. Sınıf düzeylerindeki öğrenciler ile yürütülmüştür. Çalışmada veriler hazırlanan görüşme formuyla toplanmıştır. Elde edilen veriler N-vivo 8 programı ile analiz edilmiştir. Çalışma sonucunda uzaktan eğitime yönelik olumlu görüşler, uzaktan eğitime yönelik olumsuz görüşler ve öneriler ana temalarının oluştuğu görülmüştür. Uzaktan eğitime yönelik olumlu görüşler ana teması altında uzaktan eğitimin avantajları, materyal, öğretim üyesi, ölçme ve değerlendirme alt temaları oluşmuştur. Uzaktan eğitime yönelik olumsuz görüşler temasının uzaktan eğitimin dezavantajları, materyal, öğretim üyesi, ölçme ve değerlendirme alt temalarından oluştuğu görülmüştür. Öneriler ana temasında ise katılımcıların etkileşimin artırılması, fırsat eşitliğinin sağlanması, uzaktan eğitim okuryazarlığı, yoklama, internet altyapısı, ölçme ve değerlendirmenin sağlık yürütülmesi alt temalarında görüş bildirdikleri tespit edilmiştir.

The aim of this study is to determine the views of the Faculty of Theology students towards distance education. The research was carried out with a qualitative design. Considering the structure of the study, the easily accessible case sampling method was preferred while forming the study group. The research was carried out with students at the preparatory, 1st, 2nd, 3rd and 4th grade levels of Fırat University Faculty of Theology in the 2020-2021 Spring Term. In the study, the data were collected with the prepared interview form. The obtained data were analyzed with the N-vivo 8 program. As a result of the study, it was seen that the main themes of positive opinions about distance education, negative opinions and suggestions about distance education were formed. The advantages of distance education, materials, lecturers, measurement and evaluation sub-themes were formed under the main theme of positive opinions about distance education. It has been seen that the theme of negative opinions about distance education consists of the disadvantages of distance education, material, lecturer, measurement and evaluation sub-themes. In the main theme of the suggestions, it was determined that the participants expressed their opinions on the sub-themes of increasing interaction of participants, ensuring equal opportunity, distance education literacy, polling, internet infrastructure, healthy conducting of measurement and evaluation.
Examination of the views of the faculty of theology students towards distance education during the epidemic period
Keywords: Din